EKSISTENSI MEDIA MASSA KONVENSIONAL DI TENGAH TERPAAN MEDIA BARU (NEW MEDIA) - Yulianti, Tika (MEDIASI, 2020)
The presence of new media (new media) based on Computer Mediated Communication (CMC) that relies on Internet connection is undeniable to change social order in the community. Thus, the existence of the conventional media became a question in the middle of the new media was presented in the social order. Based on Nielsen study in 2018, Indonesian consumers now spend an average of 5 hours every day consuming content, either through conventional media or the Internet. The research also shows that the TV viewing duration is still the highest, which is an average of 4 hours and 53 minutes per day, the duration of accessing the Internet is the second highest which is an average of 3 hours 14 minutes per day; followed by listening to Radio (2 hours 11 minutes), reading the newspaper (31 minutes) and reading the magazine (24 minutes). Beside that, the increase in Internet consumption makes dual-screen habits between digital media and conventional media becomes something common. There are at least 50 percent duplication between TV and Digital, 62 percent duplication on Radio vs Digital, while the print and Digital Media duplication reaches 72 percent. Based on the description, the convergence becomes one of the keys on mass media existence in the present era.Keywords: Conventional Media, New Media, Existence, Convergence, CMC, Conglomeration